A new double integral inequality and application to stability test for time-delay systems. (March 2017) - Zhao, Nan; Lin, Chong; Chen, Bing; Wang, Qing-Guo
Abstract: This paper is concerned with stability analysis for linear systems with time delays. Firstly, a new double integral inequality is proposed. Then, it is used to derive a new delay-dependent stability criterion in terms of linear matrix inequalities (LMIs). Two numerical examples are given to demonstrate the effectiveness and merits of the present result.